2011
DOI: 10.1002/ibd.21451
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of CDX2, β-catenin, and TP53 in inflammatory bowel disease-associated colorectal cancer

Abstract: In i-CRC and CD-associated SBA, carcinogenesis is associated early with p53 mutations and to inflammation intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…By IHC staining of colon cancer tissue, it has been shown that CDX2, APC, and b-catenin expression were correlated [52,65]. Especially at the invasive front, loss of CDX2 expression seems to inversely correlate with nuclear b-catenin [65].…”
Section: Cdx2 In Wnt/b-catenin Signaling and Proliferationmentioning
confidence: 96%
See 1 more Smart Citation
“…By IHC staining of colon cancer tissue, it has been shown that CDX2, APC, and b-catenin expression were correlated [52,65]. Especially at the invasive front, loss of CDX2 expression seems to inversely correlate with nuclear b-catenin [65].…”
Section: Cdx2 In Wnt/b-catenin Signaling and Proliferationmentioning
confidence: 96%
“…One study reported that CDX2 expression was inversely correlated to cytoplasmic b-catenin at the invasive front in sporadic (but not inflammatory bowel disease (IBD)-associated) tumors [52]. CDX2 expression was also inversely correlated to claudin-18 (CLDN18) expression À a component of tight junctions and a proposed oncogene [41].…”
Section: Right Versus Left Sided Tumorsmentioning
confidence: 98%
“…Increase in mucosal pro-inflammatory cytokine or other inflammatory mediators such as reactive oxygen and nitrogen species, or cyclooxygenase-2 (COX-2)-derived prostaglandins production results in alterations of a large number of molecules such as DNA, RNA, proteins or lipids. For example, they induce the formation of adducts to DNA, generating point mutations in genes like the p53 tumour suppressor gene, which is early mutated in IBD inflamed mucosa (even before neoplastic transformation) (Laurent et al, 2011), and in CpG islands involved in DNA methylation. In addition, the increase in local tissue pro-inflammatory cytokines and prostaglandins inhibits apoptosis and favours cell proliferation, thereby facilitating carcinogenesis.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Mesalamine has been reported to decrease the activity of the wingless and integration site growth factor (Wnt)/β-catenin pathway [which is constitutively activated in up to 80% of sporadic colorectal cancers due to somatic mutation of the Apc tumour suppressor gene, although lesser in CAC (Viennot et al, 2009;Laurent et al, 2011)], by inhibiting protein phosphatase A2 (which results in a enhancement of β-catenin phosphorylation, and induces activation of carcinogenetic genes such as cyclin D1, c-met and c-myc) (Bos et al, 2006). 5-aminosalicylic acid has also been reported to inhibit epidermal growth factor receptor (EGFR) pathway.…”
Section: Effects On the Wnt/β-catenin And The Epidermal Growth Factormentioning
confidence: 99%
“…For example, abnormal p53 expression was noted in a majority of IBD-associated tumors, whereas MSI-high (MSI-H) was found only in a minority of IBD-associated dysplasias and adenocarcinomas. [9][10][11] However, similar molecular studies in pouch adenocarcinoma after pouch are lacking. The aims of the study were to characterize the clinical and histomorphologic features of pouch adenocarcinoma in patients after pouch, compare them with UC-associated adenocarcinoma, examine the intactness of MMR proteins, overexpression of p53, and nuclear immunoreactivity in b-catenin (2 markers involved in the chromosomal instability pathway in colorectal cancer), and determine the cell lineage of pouch and peripouch adenocarcinoma.…”
mentioning
confidence: 99%